Review on the Prominence of SMEs in Malaysia and Its’ Imprint on University Industry Collaboration - Darshana, Kumari Raguphaty; Shamsuddin, Baharin; Faiz, Mohd Turan (Springer Nature, 2020)
Small and Medium Enterprises (SMEs) represent a very large percentage in the Malaysian economy landscape and has a huge impact on University Industry Collaborations (UIC). In many developed and developing countries, UIC have clearly benefited both the industry and university on a large scale. However, Malaysia faces a different set of challenges to overcome in establishing intensified UIC. The representation of SMEs must be considered and amplified in a collaboration between industries and universities to ensure sustainability in the collaboration and continuous innovative development of both the industry and university. Herein, this paper explores the prominence of SMEs within the Malaysian economic landscape. It further examines the differences in policy direction and supply chain management for SMEs by developed economies. Based on that parameters, this paper also discusses the imprint SMEs has on UIC.